IMPLEMENTASI MODEL BLENDED LEARNING TERHADAP KETERAMPILAN GENERIK PEMODELAN DAN HASIL BELAJAR SISWA PADA MATERI KELARUTAN DAN HASIL KALI KELARUTAN - Rahmansyah Rahmansyah; Yudha Irhasyuarna (Universitas Lambung Mangkurat, 2016)
Abstract. This study aimed to determine the effect of the learning model of blended learning generic skills learning outcomes in the modeling and chemical materials. This study used a quasi-experimental methods (quasi experiment) with the draft nonequivalent control group design. The independent variables in this study is a learning model of blended learning and conventional learning models, while the dependent variable is the generic skills learning outcomes modeling and chemistry. Subjects were students of SMA Negeri 5 Banjarmasin grade XI totaling 149 students. Sampling was done by cluster random sampling, a class XI IPA 4 as the control class and XI IPA 2 as the experimental class. The data collection technique using the test results of study, observation and student questionnaire responses. Data were analyzed using normality test, homogeneity test, t-test and N-gain. The results showed that the influence of blended learning models to modeling generic skills and student learning outcomes. Results obtained t t-test of 4.41 is greater than the price Ftable is at 2.00, it indicates that there are differences in generic skills modeling dabn significant student learning outcomes after learning blended learning models. Based on the results of data analysis can be concluded that the application of blended learning models in chemical material effect on modeling generic skills and student learning outcomes SMA Negeri 5 Banjarmasin.Keywords: Blended Learning Model, the conventional model, modeling and generic skills learning outcomes